Influences on college health provider practice for routinely screening female college students’ HPV vaccination status - Erica Liebermann; Bing Si; M. Katherine Hutchinson; Bo Li; Melissa A. Sutherland (BMC Public Health)
Abstract Background HPV vaccination is highly effective in preventing HPV infection and subsequent precancers and invasive cancers related to HPV. Unfortunately, vaccine coverage in the U.S. lags behind national and global targets. College students are an important audience for catch-up vaccination given suboptimal population coverage in adolescents. This study examined factors associated with college healthcare provider (HCP) practices for routinely screening HPV vaccination history of female college students. Methods One thousand two hundred twenty-one U.S. college HCPs completed surveys and reported on a variety of screening practices in college health centers, including assessing the HPV vaccination status of female college students. Participants included nurse practitioners, physicians, and physician assistants. Results Forty-five percent of college HCPs reported routinely screening the HPV vaccination histories of most (≥ 70%) of their female students. Nurse practitioners (NPs) were more likely than other providers to consistently assess HPV vaccination status. In multivariable logistic regression modeling, high rates of routine HPV vaccination screening were associated with NP role, more positive provider attitudes and self-efficacy toward screening, larger institutions, college-level policies, in-service trainings and electronic health record prompts that supported HPV vaccination history screening. No differences were found by other provider demographic factors, institution type or region. Conclusions College health centers present unique opportunities to identify unvaccinated female students and offer or refer them for vaccination. Future research needs to examine HPV vaccination status and screening among other types of college students and identify the multi-level factors that act as facilitators and barriers to assessing HPV vaccination status and offering the HPV vaccine.